Higienisasi Pesantren di Era Pandemi Covid-19 - Fahrudin Fahrudin; Saifuddin Zuhri Qudsy (Religi: Jurnal Studi Agama-agama, 2021)
The Covid-19 pandemic in Indonesia also had an impact on the pesantren. This article aims to conduct a study of the hygiene practices adopted by pesantren during the Covid-19 pandemic. The pesantren that were the objects of this study were Tebuireng, Daarut Tauhiid and Krapyak. The formulation of the problem of this research is how to describe hygiene in pesantren in the middle of the Covid-19 pandemic; what are the motives that make hygiene in pesantren applied; and how hygiene during the Covid-19 pandemic changed the face of the pesantren. The results of this study shows that the pesantren hygiene is carried out by actualizing and revitalizing the values of clean and healthy life contained in Islam. This is manifested in recommendations such as the application of the ethics of coughing and sneezing, often performing ablution and washing hands. Hygiene is carried out with the aim that the pesantren can help decide the spread of Covid-19 based on regulations and circulars issued by the government and Islamic organizations. As a result of the application of this hygiene, pesantren underwent a fundamental change in their routine rituals and educational orientation. The pesantren is responsible for producing students who have knowledge and sensitivity to clean and healthy lifestyles, as an absolute necessity in the pandemic.